2020
DOI: 10.1056/nejmoa2001017
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Coronavirus from Patients with Pneumonia in China, 2019

Abstract: The coronaviruses (CoVs) called the attention of the world for causing outbreaks of severe acute respiratory syndrome (SARS-CoV), in Asia in 2002-03, and respiratory disease in the Middle East (MERS-CoV), in 2012. In December 2019, yet again a new coronavirus (SARS-CoV-2) first identified in Wuhan, China, was associated with a severe respiratory infection, known today as COVID-19. This new virus is highly transmissible, and quickly spread throughout China and 30 additional countries. As result, the World Healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

174
22,715
23
1,283

Year Published

2020
2020
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25,404 publications
(24,195 citation statements)
references
References 13 publications
(7 reference statements)
174
22,715
23
1,283
Order By: Relevance
“…From genomic surveillance of clinical samples from patients with viral pneumonia in Wuhan, China, a novel coronavirus (termed 2019-nCoV) has been identified. 10,11 Our phylogenetic analysis of 2019-nCoV, sequenced from nine patients' samples, showed that the virus belongs to the subgenus Sarbecovirus. 2019-nCoV was more similar to two bat-derived coronavirus strains, bat-SL-CoVZC45 and bat-SL-CoVZXC21, than to known human-infecting coronaviruses, including the virus that caused the SARS outbreak of 2003.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…From genomic surveillance of clinical samples from patients with viral pneumonia in Wuhan, China, a novel coronavirus (termed 2019-nCoV) has been identified. 10,11 Our phylogenetic analysis of 2019-nCoV, sequenced from nine patients' samples, showed that the virus belongs to the subgenus Sarbecovirus. 2019-nCoV was more similar to two bat-derived coronavirus strains, bat-SL-CoVZC45 and bat-SL-CoVZXC21, than to known human-infecting coronaviruses, including the virus that caused the SARS outbreak of 2003.…”
Section: Discussionmentioning
confidence: 93%
“…8,9 In late December, 2019, several patients with viral pneumonia were found to be epidemiologically associated with the Huanan seafood market in Wuhan, in the Hubei province of China, where a number of non-aquatic animals such as birds and rabbits were also on sale before the outbreak. A novel, human-infecting coronavirus, 10,11 provisionally named 2019 novel corona virus (2019-nCoV), was identified with use of next-generation sequencing. As of Jan 28, 2020, China has reported more than 5900 confirmed and more than 9000 suspected cases of 2019-nCoV infection across 33 Chinese provinces or municipalities, with 106 fatalities.…”
Section: Introductionmentioning
confidence: 99%
“…Sir, Since a novel coronavirus first identified in Wuhan, Hubei province in China in December 2019, the number of cases has increased abruptly, with the infection spreading rapidly to other Chinese cities and to more than two dozen countries around the world [1]. As of 23 rd February 2020, 26 cases (16 imported and 10 indigenous) of COVID-19 had been diagnosed in Taiwan [2].…”
Section: Effective Strategies To Prevent Coronavirus Disease-2019 (Comentioning
confidence: 99%
“…12 SARS-CoV-2 (initially named 2019-nCoV) was detected in December 2019 after sequencing of clinical samples from a cluster of patients in Wuhan, China who dev -eloped pneumonia of unknown cause. 13 This outbreak is rapidly evolving and as of March 3, 2020 there have been 88 948 laboratory confirmed cases of COVID-19, with 3043 deaths (3·4% mortality). Outside China, there have been 8774 cases reported from 64 countries with 128 deaths.…”
Section: Introductionmentioning
confidence: 99%